Financing for development series: Are cash transfers a suitable alternative to energy and food subsidies? - Matthias Oschinski (Deutsches Institut für Entwicklungspolitik (DIE), 2008)
As rising energy and food prices reached their peak, subsidies have come under increased scrutiny as a means of supporting the poor. Not only do they put a severe strain on government budgets, more often than not they miss their target owing to leakages, corruption and price distortions. An alternative to subsidies may consist in conditional cash transfers to the poor. Whether they are a more efficient option for financing development goals depends, however, on a number of factors. First, conditional cash transfers are appropriate when structural poverty is, at least in part, due to a lack of demand. Second, a country needs to have both the administrative capacity for proper targeting and the means to monitor conditionalities accurately and to enforce them. Third, a viable exit strategy must be established to prevent families from falling back into extreme poverty once they become ineligible to participate. Finally, political will and public acceptance are essential for successful implementation.
Keywords: 330